Texture of materials of elements of tribological systems of machines and mechanisms in non-equilibrium processing and functioning conditions - Aulin, Viktor; Аулін, Віктор Васильович; Manko, Yehor; Манко, Єгор; Chumak, Vitaly; Чумак, Віталій; Lysenko, S.; Лисенко, Сергій Вікторович; Derkach, Oleksii; Деркач, Олексій Дмитрович; Makarenko, Dmytro; Макаренко, Дмитро Олександрович (Khmelnynskyi National University, 2025)
The article is devoted to microtexturing of metal and polymer materials of tribological system elements, its influence on the characteristics and properties of working surfaces of samples and parts. Various types of microtexture of steel and composite materials based on zirconium oxide are considered. The mechanism of their formation is clarified. Mainly, the mechanisms of microtexturing are associated with the field of tension created during friction and laser processing. It is determined that laser processing of steel samples leads to combined microtexturing and a texture gradient along the depth of the surface layer of the sample. Texture in composites is revealed both during laser processing and during friction testing. It is shown that the revealed texture positively affects the operational characteristics of parts, increasing the level of reliability and wear resistance, as well as the tribological efficiency of tribocouplings of parts of assemblies, systems, units of machines and mechanisms. Стаття присвячена мікротекстуруванню металевих і полімерних матеріалів елементів трибологічних систем, впливу його на характеристики і властивості робочих поверхонь зразків і деталей. Розглянуто різні типи мікротекстуру сталевих та композитних матеріалів на основі оксиду цирконію. З'ясовано механізм їх утворення. Переважно механізми мікротектурування зв'язують з полем напруженості, створених в процесі тертя та лазерної обробки. Визначено, що лазерна обробка сталевих зразків призводить до комбінованого мікротекстурування і градієнту текстури за глибиною поверхневого шару зразка. Виявлена текстурованість у композитах як при лазерній обробці, так і при випробуванні тертям. Показано, що виявлена текстурованість позитивно впливає на експлуатаційні характеристики деталей, підвищуючи рівень надійності і зносостійкості, а також трибологічну ефективність трибоспряжень деталей вузлів, систем, агрегатів машин і механізмів.
Текстурованість матеріалів елементів трибологічних систем машин і механізмів в нерівноважних умовах обробки та функціонування..
Keywords: steel; сталь; composite; композит; tribological system; трибологічна система; microtexturing; мікротекстурування; X-ray radiation; рентгенівське випромінювання